Crown-Containing Phthalocyanines are Potential Sensibilizers for Photodynamic Therapy. Synthesis, Properties and Role of Non-Covalent Interactions - Baulin, V.E.; Goldshleger, N.F.; Baulin, D.V.; Kalashnikova, I.P. (Biomedical Chemistry: Research and Methods, 2018)
Phthalocyanines (Pc) and their supramolecular aggregates are widely used in molecular electronics, chemical sensors, and catalysis, as well as in biology and medicine, including photodynamic therapy (PDT). One of the possibilities of preventing Pc aggregation in an aqueous medium is using surfactants: with their molecules are self-organized various supramolecular complexes. This results in formation of the required microheterogeneous Pc environment compatible with the biological medium. The monomolecular state of Pc in an aqueous medium is especially important for their use as sensitizers in fluorescence diagnostics and PDT. We have summarized here the results of investigations of distinctive features of the supramolecular aggregation of octa-[(4′-benzo-15-crown-5)oxy]phthalocyaninates (Mcr8Pc) and tetra-[(4′-benzo-15-crown-5)oxy]phthalocyaninates (Mcr4Pc) in electrolytic solutions and solutions of synthetic cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS), sodium dodecylbenzenesulfonate (SDBS). Biocompatible surfactants such as carboxymethylcellulose sodium salt (Na-CMC) and sodium deoxycholate (SDC) were also studied. Using the electron absorption spectra it has been shown that formation of Mсr8Pc monomers in micellar solutions of SDC is affected by both increased surfactant concentration and by changes in the ionic strength of solution after sodium chloride is added. The effect of the chemical structure of the biocompatible anionic surfactant on monomerization of crown_containing phthalocyanines has been identified; this fact opens new possibilities for using this family of compounds for fluorescent diagnosis and PDT.